No to distance education! Production of meaning of discourses of nursing representative entities - Marina da Silva Sanes; Franciele Budziareck das Neves; Lenna Eloisa Madureira Pereira; Flávia Regina Souza Ramos; Laura Cavalcanti de Farias Brehmer; Mara Ambrosina de Oliveira Vargas; Jussara Gue Martini (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the processes of production of meanings, based on the positions of Brazilian nursing representative entities, on distance education, considering the implications for nursing as a discipline, profession and work. Methods: this documentary research was carried out in sources from the Federal Nursing Council and Associação Brasileira de Enfermagem, from 2015 to 2018. Data were examined from discourse analysis, using paraphrase and polysemy as analytical devices. Results: they were organized based on the effects of meanings produced and affiliated to two analytical categories: "Forms of mobilization and operating entities" and "Basis and justifications for the positions". Final Considerations: the discourses signal concern about the future training of new professionals. Resistance, participation, visibility, broad and emphatic debate on the topic are shown as strategies for coping and defending a training process less captured by neoliberal logic, and more relational and committed to the quality of health care.